Mobility and Rural Development: Migrants' Collective Action in Central Mexico - Chavez, Alejandro Rosendo (2023)
International migration as a fact of mobility is a factor of transformation in contemporary societies, for its part, the approach to territorial rural development is built with the participation of people living in the territory, taking into account even absent people, who help in the reproduction of society. The associations of natives are precisely a manifestation of how migration and participation have contributed to community development in migratory territories. Through a qualitative approach (open questionnaires and semi-structured interviews) with various actors from the municipality of Almoloya de Alquisiras, in the period 2017 to 2020. The results show that in the community of origin there are individual and collective actions, which are aimed at rural development, but with limited results so far, due to lack of synergy with the other actors of the territory and the lack of training of decision makers in the local public administration.